NEED ASSESSMENT OF PARENTS WITH AUTISTIC CHILDREN - NASREEN BANU, ROSALIN MISHRA, P. SREEDEVI and (The Journal of Research, PJTSAU, 2019)
Autism is a neurobiological disorder, which affects the brain and thereby the whole body. It is reflected in terms bodily impairments such as deficits in social relations, communication with repetitive and self stimulatory behaviors. Unique characteristics of autistic children create many unique challenges to parents. These parents are under going through lot of stress in dealing with their autistic children. Research studies revealed that parents of autistic children with lower income have more unmet needs than the parents with higher income (Brezis et al. 2015; Hodgetts, Zwaigenbaum and Nicholas, 2015). Thus presence of an autistic child in the family has a multidimensional effect in varied ways such as generating special needs not only for the child but also for the parents at personal or social or at wider community level. Though parents take the key role in taking care of the children and the families at the root level, their needs are often overlooked in research. In Indian studies not much emphasis has been put on parent’s general as well as specific needs. This area of study is almost non- existent in the state of Telangana. Therefore the present study was undertaken to assess the needs of parents with autistic children.